Silicified microcrystalline cellulose based pellets and their physicochemical properties. Issue 33 (18th May 2016) - Mustafa, Oluwabukola; Chaw, Cheng Shu
ABSTRACT: Silicified microcrystalline cellulose (SMCC), Prosolv SMCC 50 was used as spheronization aid to manufacture pellets by extrusion and spheronization. Different ratios of SMCC to lactose were used to manufacture pellets using appropriate levels of water as liquid binder. Avicel PH101 based pellets were also manufactured for comparison of their physical properties. The ratio of liquid binder to spheronization aid was critical to produce pellets of desired size and shape. Extrudates composed of 20% aid could withstand only smaller spheronization force in order to be shaped into pellets. The successful products fulfilled the quality of pellets such as narrow size distribution and spherical in shape. The highest surface tensile strength was observed in pellets with equal ratio of lactose to SMCC while pellets having 20% aid disintegrated rapidly within 15 min. Furthermore, Prosolv SMCC 50 based pellets possessed a stronger surface tensile strength when compared with Avicel PH101 based pellets. In conclusion, Prosolv SMCC 50 has showed to be a good spheronization aid for extrusion and spheronization when used in the range of 20 to 80% content. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43829. Abstract :